2011
DOI: 10.4103/0377-4929.77333
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of bacteriophages to multi-drug resistant Enterococci obtained from diabetic foot: A novel antimicrobial agent waiting in the shelf?

Abstract: Multidrug-resistant Enterococci are a real problem and continuous surveillance is necessary. Today, resistance has rendered most of the original antibiotics obsolete for many infections, mandating the development of alternative anti-infection modalities. One of such alternatives stemming up from an old idea is the bacteriophage therapy. In the present study, we could able to demonstrate the viable phages against MDR E. faecalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
12
1
Order By: Relevance
“…About 30% of the enterococcal strains isolated from our patients were revealed as high level aminoglycoside resistant (HLAR); in contrast, there were no alarm strains resistant to glycopeptides (VRE -vancomycin-resistant Enterococcus). These values are lower than previously presented in the available literature [14][15][16][17]. In most cases the material was obtained immediately on admission to the clinic, and a relatively low fraction of HLAR strains were recovered, both of which contradict the nosocomial source of enterococcal infection.…”
Section: Discussioncontrasting
confidence: 48%
“…About 30% of the enterococcal strains isolated from our patients were revealed as high level aminoglycoside resistant (HLAR); in contrast, there were no alarm strains resistant to glycopeptides (VRE -vancomycin-resistant Enterococcus). These values are lower than previously presented in the available literature [14][15][16][17]. In most cases the material was obtained immediately on admission to the clinic, and a relatively low fraction of HLAR strains were recovered, both of which contradict the nosocomial source of enterococcal infection.…”
Section: Discussioncontrasting
confidence: 48%
“…This can be attributed to the fact that these organisms have been exposed to multiple antibiotics in hospital settings, thus providing them with an evolutionary pressure for selective advantage (reviewed in Moellering, 1992). As already stated, the enterococci have evolved mechanisms for the transfer of resistance genes through exchanging plasmids via conjugation, as well as exchanging resistance genes on transposons or via bacteriophages (Clewell, 1990;Dunny, 1990;Scott, 1992;Clewell, 1993;reviewed in Jett et al, 1994;Mazaheri Nezhad Fard et al, 2011;Vinodkumar et al, 2011). Mutations can also lead to high-level resistance to various antibiotics.…”
Section: Antibiotic Resistance To Antimicrobial Agentsmentioning
confidence: 94%
“…Finally, the last conjugative system involves transposons found in Gram-negative and Gram-positive bacteria (reviewed in Scott, 1992 andPalmer et al, 2010). Apart from these conjugative systems, infection with bacteriophages is another method of genetic material exchange used by enterococci to allow for the spread of virulence factors or antibiotic resistance (Mazaheri Nezhad Fard et al, 2011;Vinodkumar et al, 2011).…”
Section: Pathogenesismentioning
confidence: 99%
“…from 287 microorganisms isolated from diabetic foot infections. In India, Vinodkumar et al, (2011) found that a whole of 65.6% of Enterococcus spp. were isolated from diabetic foot infections with high level aminoglycoside resistance (HLAR).…”
Section: Enterococcus Virulence Genesmentioning
confidence: 99%
“…In Germany, Werner et al, (2012) stated that 64 E.faecalis and 37 E. faecium isolates did not show a particular multi resistance phenotype and resistances to glycopeptides and antibiotics. Moreover, in India, Vinodkumar et al, (2011) conveyed that a total of 65.6% of Enterococcus spp. showed HLAR.…”
Section: Aminoglycoside Resistancementioning
confidence: 99%